Professional Allowances, Motivation, and the Construction of Teacher Performance in the Digital Education Era - Andi Zulitsnayarti Mardhani Syam; Adiningsih, Sri Hutami; Damasinta, Alfiana; Pratama, Is Arianto (Jurnal Penelitian Multidisiplin Bangsa, 2025)
The transition to the digital education era requires teachers to play a role as learning facilitators that is responsive, adaptive, and capable of accommodating the dynamics of change in the teaching and learning process. In this context, teacher professional allowances are expected to serve as a means to enhance welfare while also promoting the professionalism of educators. This paper aims to explore the relationship between professional allowances, work motivation, and the construction of teacher performance in facing educational challenges in the digital era. Using a descriptive-qualitative approach based on literature review, this article examines the extent to which professional allowances can drive teachers' internal motivation and shape professional performance in line with the demands of digital transformation. The findings indicate that targeted allowance provision can enhance work enthusiasm, innovation in learning, and overall teacher performance quality. However, issues such as complex administrative burdens in the disbursement process and suboptimal distribution remain obstacles that need to be addressed. Therefore, more efficient, inclusive professional allowance policies are necessary to meet teachers' needs for professional development in the digital era.